Implementasi Fuzzy K-Nearest Neighbour (FK-NN) Untuk Pemilihan Keminatan Mahasiswa Teknik Informatika (Studi Kasus : Program Studi Teknik Informatika Fakultas Ilmu Komputer Universitas Brawijaya) - Dhony Lastiko Widyastomo; Indriati Indriati; Rizal Setya Perdana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Concentration selection is one of few steps for a students to finish their studies. Informatics programee have 4 concentration consist of Artificial Inteligent(AI), Software Engineering (SE), Network and Game. Unfortunately because the limited and many internal problems from the students causing some problem for the concetration selection. To solve the problem of selection, a system who can give a classification is needed to give the solution. A classification for concentracion selection uses fuzzy k-nearest neighbor for its method. The method works with calculate the number of K value to Process the classification of 4 study concentration and resulting the recomendation class of concentration class based on the student data. Based on the research of study using 200 data of the students of Informatics engineering, from 2011 to 2013, the biggest accuracy was produced by K value=3 and have 87,5% accuracy. While the lowest precentages of accuracy was produced by K value=10 with the averages of 67,5% accuracy.